Translanguaging in Efl Classroom: Reasons and Impacts - Efendi, Marzon; Syafryadin (Universitas Nusantara PGRI Kediri, 2024)
Translanguaging is an educational method that involves using two languages or more interchangeably for both receiving and producing information within a single activity. In Kurikulum Merdeka, English becomes one of the compulsory subjects for elementary school students. The lack of vocabularies and other factors support the elementary school English teacher to employ translanguaging in the education setting. This research aims to explore the reasons and impacts of translanguaging usage in the classroom. The kind of this research is descriptive qualitative research. The researcher involved three English teachers from one of Sekolah Penggerak Batch 1. The researcher employed two data collection techniques (open-ended questionnaires and semi-structured interviews). The results are there are eight reasons of translanguaging in EFL classroom, namely the lack of vocabularies mastery, to make the instruction clearer for the students, to engage the students and make them active, to create a comfort and joyful learning environment, to avoid misconception of learning materials, the students’ request, the limitation of time in EFL classroom, and to reduce students’ anxiety. There are five impacts of translanguaging, namely making the students become more active, the learning objective can be reached optimally, the students’ English skills and comprehension get better, the students can understand the instruction well, and the students can enjoy the learning process. The researcher suggests the next researcher to conduct the research about the practice of translanguaging in elementary school.